2022
DOI: 10.3390/bios12020079
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effect of Terahertz Waves in C57BL/6 Mice

Abstract: Terahertz is a new radiation source with many unique advantages. In recent years, its application has rapidly expanded to various fields, but there are few studies on the individual effects of terahertz. In this study, we investigated the behavioral effects of terahertz radiation on C57BL/6 mice, and we conducted an open field test, an elevated plus maze test, a light–dark box test, a three-chamber social test, and a forced swim test to explore the effects of terahertz radiation on mice from a behavioral persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, this study found that terahertz radiation at 0.138 THz and 2 mW promotes synaptic transmission in the hippocampal CA1 region. At the in vivo level, Miao et al increased terahertz radiation power to 90 mW and observed that 0.14 THz radiation reduces anxiety and depression symptoms in mice while enhancing their social behavior [ 65 ]. Some studies have also used backward wave oscillators and quantum cascade lasers as terahertz sources, but these investigations are often limited to the cellular level.…”
Section: Methods For Terahertz Radiation Regulation Of Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study found that terahertz radiation at 0.138 THz and 2 mW promotes synaptic transmission in the hippocampal CA1 region. At the in vivo level, Miao et al increased terahertz radiation power to 90 mW and observed that 0.14 THz radiation reduces anxiety and depression symptoms in mice while enhancing their social behavior [ 65 ]. Some studies have also used backward wave oscillators and quantum cascade lasers as terahertz sources, but these investigations are often limited to the cellular level.…”
Section: Methods For Terahertz Radiation Regulation Of Neuronsmentioning
confidence: 99%
“…Previous research has indicated that terahertz radiation can impact the morphology and functionality of neurons, and these effects are related to factors such as terahertz frequency, duration, and power [ 64 , 65 , 66 ]. Therefore, to further select appropriate terahertz radiation protocols, it is essential to analyze the distribution of research subjects and terahertz radiation protocols in the relevant literature.…”
Section: Methods For Terahertz Radiation Regulation Of Neuronsmentioning
confidence: 99%
“…Terahertz (THz) EMR is typically used in security screening, astronomy, tumor imaging, and biomedicine. Further, a recent in vivo study suggested that THz radiation increased antidepression, anti-anxiety, and social interactions in exposed mice [ 64 ]. Moreover, THz EMR has been reported to cause death of human primary and malignant cells [ 65 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%
“…Recent studies have found that THz irradiation can change the behavioral phenotype of mice to a certain extent; however, the effect of terahertz irradiation on neural stem cells in mice has not been studied. 35 Therefore, we first investigated the effects of THz irradiation on mNSCs, and we further selected hNSCs derived from iPSCs to investigate the biological effects of THz irradiation. In this study, flow cytometry was used to analyze proliferation and apoptosis in neural stem cells, and immunofluorescence was used to analyze DNA damage in neural stem cells.…”
Section: Introductionmentioning
confidence: 99%